Does it matter who extorts? Extortion by competent and incompetent enforcers. (15th September 2021) - Samuel, Andrew; Mishra, Ajit
Abstract: This paper offers a novel explanation for extortion, which is the practice of demanding payments from compliant agents by law‐enforcement officers. Namely, that extortion occurs due to the officer's incompetence, where the competence level is endogenous. Because competence improves enforcement, extortion affects deterrence directly by weakening agents' incentive to be compliant and indirectly by affecting officers' incentives to become competent. Accordingly, the harmful effects of extortion on deterrence depend on whether the competent or incompetent officer extorts. We show that extortion by incompetent officers is the lesser of the two evils, compared to bribery.